2020
DOI: 10.1002/jmv.26339
|View full text |Cite
|
Sign up to set email alerts
|

Newly diagnosed diabetes mellitus, DKA, and COVID‐19: Causality or coincidence? A report of three cases

Abstract: Novel coronavirus disease 2019 (COVID‐19), a 2020 pandemic, has resulted in an unexpected loss of lives, quality of life, and economy. The COVID‐19 clinical spectrum varies from asymptomatic to death, and its complications may involve various organs. Notwithstanding, the impact of COVID‐19 on endocrine systems is understudied. Previous coronavirus outbreak such as SARS‐CoV can cause new‐onset diabetes mellitus (DM). However, there were only two previous case reports on newly diagnosed DM in COVID‐19 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 11 publications
5
74
1
5
Order By: Relevance
“…Epidemiology and clinical manifestations. Diabetic ketoacidosis (DKA) has been observed in patients without known diabetes mellitus weeks to months after resolution of COVID-19 symptoms 182 . It is not yet known how long the increased severity of pre-existing diabetes or predisposition to DKA persists after infection, and this will be addressed by the international CoviDiab registry 183 .…”
Section: Endocrine Sequelaementioning
confidence: 99%
“…Epidemiology and clinical manifestations. Diabetic ketoacidosis (DKA) has been observed in patients without known diabetes mellitus weeks to months after resolution of COVID-19 symptoms 182 . It is not yet known how long the increased severity of pre-existing diabetes or predisposition to DKA persists after infection, and this will be addressed by the international CoviDiab registry 183 .…”
Section: Endocrine Sequelaementioning
confidence: 99%
“…People with diabetes are at a higher risk for more severe COVID-19 symptoms, hospitalization, and mortality compared with the general population. [1][2][3][4] Recent case reports have associated COVID-19 disease with the onset of type 1 diabetes [5][6][7] ; however, the evidence remains limited and inconsistent. [8][9][10] We developed a highly sensitive and specific test to measure COVID-19 antibodies and applied this assay to people with new-onset and established type 1 diabetes as well as children and adults from the underlying general population during the current pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This type of presentation has been reported by many authors ( 3 , 21 , 22 , 23 , 24 , 25 , 26 ) ( 27 ) but its prevalence and features remain poorly researched. A retrospective cohort of 35 patients with COVID-19(T2DM;28, T1DM;5, new presentation;2), presenting with DKA (31·4%), mixed DKA and HHS (37·1%), HHS (5·7%), or hyperglycaemic ketosis (25·7%) were included and evaluated in a study reported from UK ( 21 ).…”
Section: Introductionmentioning
confidence: 70%
“…The requirement of insulin gradually diminished after about 4-6 weeks of diagnosis and then hyperglycemia was controlled with oral anti-hyperglycemic drugs alone ( 23 , 24 ). Another, albeit rarer variety of patients are those who present with new-onset marked hyperglycemia with ketonuria and very mild COVID-19 infection ( 25 , 26 ). The patient, reported by us was managed on small doses of oral anti-hyperglycemic treatment ( 25 ).…”
Section: Introductionmentioning
confidence: 99%